Kinematic adjustments in the basketball free trow performed with a reduced hoop diameter rim - Khlifa, R.; Aouadi, R.; Hermassi, S.; Chelly, M. S.; Jlid, C.; Gabbett, T. J. (International Journal of Sports Science and Coaching, 2012)
The aim of this study was to investigate the effect of free throw shooting with a reduced diameter rim (diameter 0.35 m) upon the kinematics of basketball free throws. Ten basketball players (mean ± SD age 17.1 ± 0.7 years, height 1.85 ± 0.23 m, body mass 78.8 ± 5.8 kg) performed 8 "clean" successful free throws; 4 in a standard rim (diameter = 0.45 m), and 4 in a reduced diameter rim (diameter = 0.35 m). Ball release angle, ball release speed, ball release height and angles at release in elbow, shoulder, trunk, knee and ankle joints were determined for each subject. Statistical analysis showed significant increases in ball release angle, in ball release speed, in shoulder joint angle at release (p > 0.05) in any other determined parameter between the standard and reduced rim conditions. The increase of the minimum entry angle of the ball through the rim, caused by the 0.10 m reduction in diameter of the standard rim, resulted in subjects performing clean successful free throws with higher release angles and consequently with higher release speeds. The reduced hoop diameter rim can be used as an aid in training of young basketball players. Specifically, this constraint may act to increase ball release angle in basketball players with low percentage of successful free throws and when the principal cause of decreased free throws accuracy is due to a shot technique with low release angle.